2023
DOI: 10.3389/fnhum.2023.1129254
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness on level of consciousness of non-invasive neuromodulation therapy in patients with disorders of consciousness: a systematic review and meta-analysis

Abstract: BackgroundDisorders of consciousness (DoC) commonly occurs secondary to severe neurological injury. A considerable volume of research has explored the effectiveness of different non-invasive neuromodulation therapy (NINT) on awaking therapy, however, equivocal findings were reported.ObjectiveThe aim of this study was to systematically investigate the effectiveness on level of consciousness of different NINT in patients with DoC and explore optimal stimulation parameters and characteristics of patients.MethodsP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…From another clinical perspective, our results showing that 2 mA anodal PFC tDCS can positively influence the dynamic signatures of consciousness during anesthesia, are also consistent with the beneficial effects of such stimulation reported in DOCs patients (e.g., (Thibaut et al 2014;Angelakis et al 2014)). For instance, recent meta-analyses have concluded that tDCS is more effective in improving the level of consciousness in patients with a minimally conscious state (MCS) than in those with an unresponsive wakefulness syndrome (UWS), which is a more severe form of this medical condition (Xu et al 2022;Liu et al 2023). Our results support the efficacy of tDCS in improving consciousness markers in patients with DOCs, particularly in the least severely affected patients, and encourage the design of new clinical trials to investigate the effects of higher stimulation intensities.…”
Section: Cathodal Prefrontal Hd-tdcs Strongly Perturbed Cortical Brai...mentioning
confidence: 99%
“…From another clinical perspective, our results showing that 2 mA anodal PFC tDCS can positively influence the dynamic signatures of consciousness during anesthesia, are also consistent with the beneficial effects of such stimulation reported in DOCs patients (e.g., (Thibaut et al 2014;Angelakis et al 2014)). For instance, recent meta-analyses have concluded that tDCS is more effective in improving the level of consciousness in patients with a minimally conscious state (MCS) than in those with an unresponsive wakefulness syndrome (UWS), which is a more severe form of this medical condition (Xu et al 2022;Liu et al 2023). Our results support the efficacy of tDCS in improving consciousness markers in patients with DOCs, particularly in the least severely affected patients, and encourage the design of new clinical trials to investigate the effects of higher stimulation intensities.…”
Section: Cathodal Prefrontal Hd-tdcs Strongly Perturbed Cortical Brai...mentioning
confidence: 99%
“…In the invasive brain stimulation, only Schiff et al demonstrated the efficacy of DBS in this particular patient through strictly design (Schiff et al, 2007). On the contrary, recent systematic review showed that NINT appeared to be effective interventions for improving MCS patients (Feng et al, 2020;Liu et al, 2023). In particular, tDCS has been shown through well-designed studies to have a limited capacity for enhancing functional recovery (Thibaut et al, 2014;Martens et al, 2018).…”
Section: Mcsmentioning
confidence: 99%
“…Among non-invasive methods, transcranial direct current stimulation (tDCS) ( Zaninotto et al, 2019 ), transcranial magnetic stimulation (TMS) ( O’Neal et al, 2021 ), Transcutaneous auricular vagus nerve stimulation (taVNS) ( Hakon et al, 2020 ), and median nerve stimulation (MNS) ( Feller et al, 2021 ) have been widely adopted and used in clinical samples. In a series of therapeutic methods for promoting rehabilitation, neuromodulation technology has a direct or indirect regulatory effect on functional connectivity between different brain regions by regulating cortical excitability and neural plasticity ( Feng et al, 2020 ; Liu et al, 2023 ). Over the past decade, the observed surge in publications clearly indicates that neuromodulation technology has been established as valuable tools for studying DOC.…”
Section: Introductionmentioning
confidence: 99%